Kissing, fellatio, and analingus as risk factors for oropharyngeal gonorrhoea in men who have sex with men: A cross-sectional study - Julien Tran; Jason J. Ong; Catriona S. Bradshaw; Marcus Y. Chen; Fabian Y.S. Kong; Jane S. Hocking; Ei T. Aung; Kate Maddaford; Christopher K. Fairley; Eric P.F. Chow (EClinicalMedicine, 2022)
Summary: Background: Our aim was to determine whether exposure to the anatomical sites (oropharynx, penis, or anus) of male partners of men who have sex with men (MSM) were independent risk factors for oropharyngeal gonorrhoea after adjusting for exposures to these sites. Methods: In this cross-sectional study, we invited MSM who attended the Melbourne Sexual Health Centre (MSHC) in Victoria, Australia between 26-November 2018 and 31-December 2020 to complete a survey of their sexual practices in the past three months. We collected data on the number of male partners with whom men engaged in sexual activities that exposed their oropharynx to their partners’ oropharynx (kissing), penis (fellatio), and anus (rimming or analingus). Only men who were aged ≥16 years, tested for oropharyngeal gonorrhoea and did not have indeterminate or invalid results were included in the final analysis. We conducted univariable and multivariable logistic regression analyses to investigate associations between oropharyngeal gonorrhoea and the three exposures to the oropharynx. Findings: The median age of the 2,322 men who completed the survey was 31 years (IQR: 26-40), and 5·2% (n = 120) were diagnosed with oropharyngeal gonorrhoea. Our univariate analysis showed that oropharyngeal gonorrhoea was significantly associated with increasing number of kissing (ptrend<0·0001), rimming (ptrend<0·0001) and fellatio (ptrend<0·0001) partners. After adjusting for all three exposures, oropharyngeal gonorrhoea was associated with increasing number of kissing (ptrend =0·014) and rimming partners (ptrend = 0·037) but not fellatio (ptrend = 0·61). Interpretation: Our data suggest kissing and rimming are important practices in oropharyngeal gonorrhoea transmission in MSM Novel interventions which target the oropharynx are required for gonorrohoea prevention. Funding: Australian National Health and Medical Research Council.